2020
DOI: 10.3390/medicina56120692
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound (CEUS) for the Evaluation of Bosniak III Complex Renal Cystic Lesions—A 10-Year Specialized European Single-Center Experience with Histopathological Validation

Abstract: Background and objectives: The aim of the present retrospective single-center study is to evaluate the diagnostic performance of contrast-enhanced ultrasound (CEUS) for assessing Bosniak III complex renal cystic lesions with histopathological validation. Materials and Methods: 49 patients with CEUS-categorized Bosniak III renal cystic lesions were included in this retrospective study. All patients underwent native B-mode, Color Doppler, contrast-enhanced ultrasound (CEUS) between 2010–2020. Eight and five pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Findings initially assessed as 2F by CT and/or MRI were the main object of reclassification among CRC, which occurred in 72.2% of assignments, either on the side of downgrading or upgrading (52.8 and 46.2% of the reclassified cases, respectively). This is in accordance with previous results by Schwarze et al, 19 and matches with the expectedly high sensitivity of CEUS we observed. 13,20–22 The reclassification rate we found in the CRC group was higher compared to what previously shown (10–20%).…”
Section: Discussionsupporting
confidence: 94%
“…Findings initially assessed as 2F by CT and/or MRI were the main object of reclassification among CRC, which occurred in 72.2% of assignments, either on the side of downgrading or upgrading (52.8 and 46.2% of the reclassified cases, respectively). This is in accordance with previous results by Schwarze et al, 19 and matches with the expectedly high sensitivity of CEUS we observed. 13,20–22 The reclassification rate we found in the CRC group was higher compared to what previously shown (10–20%).…”
Section: Discussionsupporting
confidence: 94%
“…In the case of Bosniak III cysts, which are defined as indeterminate cystic masses with thickened irregular walls or septa with enhancement and which have an approximately 50% chance of being malignant [ 9 ], partial or radical nephrectomy is warranted. Existing non-invasive methods of reducing the number of unnecessary nephrectomies are suboptimal, as highlighted by a recent study evaluating contrast-enhanced ultrasonography (CEUS), which reported that only 63% of CEUS-diagnosed Bosniak III cysts were malignant after partial or radical nephrectomy [ 36 ]. Whether SERS is also able to differentiate between benign and malignant cystic lesions is currently unknown and will require future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CEUS had a sensitivity of 100% and a NPV of 100 %, but it has the limitation that the results are dependent on the observer's previous CEUS experience. [24][25][26][27] Since standardized and specific molecular imaging-related criteria for CEUS are lacking, the reproducibly of the Bosniak classification using this technique is dependent on the experience and criteria applied by the on-site ultrasonographer. 28 In the present study, renal CEUS examinations were performed or supervised by a single skilled nephrologist (SA) with more than 20 years of clinical experience in renal ultrasound and more than 10 years CEUS experience in transplanted or native kidneys.…”
Section: Discussionmentioning
confidence: 99%